ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK HIBURAN DAN PAJAK HOTEL DALAM MENINGKATKAN PAD KOTA KENDARI - Nita Irawati; Pasrun Adam; Angelina Yenny Ringan (Sigma: Journal of Economic and Business, 2022)
The reaearch of this study was to determine and analyze: 1) The level of effectiveness of the entertainment tax in increasing the local revenue of Kendari City; 2) The level of effectiveness of hotel taxes in increasing the local revenue of Kendari City; 3) Contribution of entertainment tax in increasing local revenue of Kendari City; 4) The contribution of hotel tax in increasing the local revenue of Kendari City. Based on the results of the study, it is known that 1) The effectiveness of Kendari City's entertainment tax revenue for the 2016-2020 budget year the effectiveness of entertainment tax realization has very effective criteria; 2) The effectiveness of Kendari City hotel tax revenue for the 2016-2020 fiscal year has very effective criteria; 3) The Kendari City entertainment tax contribution for the 2016-2020 fiscal year shows that the entertainment tax contribution shows very low criteria. although the contribution of the entertainment tax is considered very low in its contribution, it can still affect Kendari City's Original Regional Revenue; 4) The Kendari City hotel tax contribution for the 2016-2020 fiscal year shows that the entertainment tax contribution shows very low criteria, although the hotel tax contribution is considered very less in its contribution to the Kendari City Regional Original Revenue.